2010
DOI: 10.1074/jbc.a109.804144
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal: AMP-activated protein kinase contributes to UV- and H2O2-induced apoptosis in human skin keratinocytes.

Abstract: We suggest that subscribers photocopy these corrections and insert the photocopies in the original publication at the location of the original article. Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…AMPK activation has been shown to mediate its procell apoptosis effects primarily through modulating its multiple downstream targets including regulating JNK [14,19,22], p53 [9,23] and inhibiting mTORC1 [7,10,13,24]. For example, it has been reported that sustained AMPK activation leads to JNK activation which is required for the induction of apoptosis in liver cells [19]; our previous study also found that activation of AMPK is involved in vincristine-induced cell apoptosis in B16 melanoma cell by mTORC1 inhibition and p53 induction [25].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…AMPK activation has been shown to mediate its procell apoptosis effects primarily through modulating its multiple downstream targets including regulating JNK [14,19,22], p53 [9,23] and inhibiting mTORC1 [7,10,13,24]. For example, it has been reported that sustained AMPK activation leads to JNK activation which is required for the induction of apoptosis in liver cells [19]; our previous study also found that activation of AMPK is involved in vincristine-induced cell apoptosis in B16 melanoma cell by mTORC1 inhibition and p53 induction [25].…”
Section: Introductionmentioning
confidence: 91%
“…AMPK phosphorylates and activates TSC2 (Tuberous sclerosis protein 2), eventually leading to mTORC1 inhibition and cell apoptosis [13,37,41,42]. Therefore, next the possible effects of Doxorubicin on mTOC1 in H9c2 cells are tested.…”
Section: Ampk Activation Is Involved In Doxorubicin-induced Jnk Activmentioning
confidence: 99%
See 3 more Smart Citations